Acute anoxia stimulates proliferation in adult neural stem cells from the rat brain - Bürgers, Heinrich; Schelshorn, Dominik W.; Wagner, Wolfgang; Kuschinsky, Wolfgang; Maurer, Martin H. (Experimental brain research, 2008)
Hypoxic-ischemic damage is a major challenge for neuronal tissue. In the present study, we investigated the effects of anoxia and glucose deprivation on adult neural stem cells (NSCs) in vitro. We assessed glucose deprivation, anoxia and the combination of the latter separately. After 24 h of anoxia, cell numbers increased up to 60% compared to normoxic controls. Whereas nearly all normoxic cells incorporated the mitotic marker BrdU (99%), only 85% of the anoxic cells were BrdU-positive. Counting of interphase chromosomes showed 8-fold higher cell division activity after anoxia. The number of necrotic cells doubled after anoxia (14% compared to 7% after normoxia). Apoptosis was measured by two distinct caspases assays. Whereas the total caspase activity was reduced after anoxia, caspase 3/7 showed no alterations. Glucose deprivation and oxygen glucose deprivation both reduced cell viability by 56 and 53%, respectively. Under these conditions, total caspases activity doubled, but caspase 3/7 activity remained unchanged. Erythropoietin, which was reported as neuroprotective, did not increase cell viability in normoxia, but moderately under oxygen glucose deprivation by up to 6%. Erythropoietin reduced total caspase activity by nearly 30% under all the conditions, whereas caspase 3/7 activity was not affected. Our results show that anoxia increases proliferation and viability of adult NSCs, although a fraction of NSCs does not divide during anoxia. In conclusion, anoxia increased cell viability, cell number and proliferation in NSCs from the rat brain. Anoxia turned out to be a highly stimulating environmental for NSCs and NSCs died only when deprived of glucose. We conclude that the availability of glucose but not of oxygen is a crucial factor for NSC survival, regulating apoptotic pathways via caspases activity other than the caspases 3/7 pathway. Therefore, we conclude that NSCs are dying from glucose deprivation, not from hypoxic-ischemic damage.
Gesehen am 30.04.2021